An analysis of language of attitude in sample answers of toefl ibt independent speaking task 1 under the appraisal framework - Võ Đặng Hoàng Uyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The thesis aims to investigate the language of Attitude, one of the three subsystems of the Appraisal theory in sample answers of TOEFL iBT Independent speaking task 1. In order to conduct the study, the descriptive analysis with the combination of both qualitative and quantitative research methods was adopted. The data for study was built up with 100 samples answers of TOEFL iBT Independent speaking task 1. The study examined 824 instances of the attitudinal words used to explore the semantic features and linguistic realizations of Attitude expressions recognized in the sample answers. Semantically, the data were classified and analyzed in the light of Appraisal Theory. In terms of Functional Grammar, the data were categorized into linguistic realizations of Attitudinal expressions as different word classes functioning to code the process and participants. The study found that the speaker as test-takers used lexical resource of Attitude to express his/her evaluation in responding to questions in three semantic category of Appraisal, namely Affect, Appreciation and Judgement. The distribution of the use of attitudinal expressions in the three category of Appraisal reflected dominance of Appreciation (76.7%) over the other ones – Affect (18.81%) and Judgment (4.49%). Several implications and suggestions on learning and teaching English for the TOEFL iBT Speaking Test Task 1, especially the language of Attitude in particular and Appraisal language in general were put forward